Literasi Media Sosial Memoderasi Pengaruh Daya Tarik Repositioning DP Mall Semarang Terhadap Frekuensi Kunjungan - Dhurotun Nasikhah; Linda Kusuma (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The DP Mall Semarang shopping center before 2018 looked empty from visitors, because the mall was considered unattractive. Tenant choices, building designs, and facilities are considered less attractive for consumers to visit. However, in mid-2018 DP Mall Semarang carried out a repositioning by renovating the building and adding international tenants and brands. DP Mall also uses social media Instagram to reach consumers because it is easier and cheaper. This study aims to determine whether the repositioning attractiveness of DP Mall Semarang can affect the frequency of consumer visits. Then social media literacy is used which is expected to strengthen the influence of the attractiveness of repositioning on the frequency of visits, because researchers see that social media literacy is currently very much needed in social media. This type of research is quantitative by distributing questionnaires to 152 visitors to DP Mall Semarang. The analysis technique used is descriptive analysis and Moderated Regression Analysis (MRA) using the SPSS application. The results showed that repositioning attractiveness had a positive effect on the frequency of visits. However, high consumer social media literacy can weaken the effect of repositioning attractiveness on the frequency of consumer visits.